IDENTIFICATION OF TYPES AND VOLUMES OF FISH PRODUCTION IN THE FISHERIES SECTOR UPT PPP PONDOKDADAP, MALANG REGENCY - Ariefandi, Muhammad Fikri; Kudrati, Amelinda Vivian; Tyas, Herlin Widi Aning; Al Maky, Nuril Huda; Yorarizka, Putri Devi; Pangestu, Wanda Suryani; Putri, Berlania Mahardika; Fathah, Aulia Lanudia; Isdianto, Andik; Setyanto, Arief; Andrimida, Anthon (Directorate of Research and Community Service (DRPM), 2023)
The fisheries sector is one of the sectors with great potential for the Indonesian economy. East Java has a large fishing enterprise, which is due to the spread of fish landing bases and an active role in promoting local fishing production, one of which is the beach fishing port (PPP) Pondokdadap. The aim of this study is to obtain information on the types and volumes of fish production captured in the PPP Pondokdadap in May and June 2022. The method used by the author in conducting this research is a qualitative-descriptive approach. According to the results of research, during May 2022, the production of fish captured in PPP Pondokdadap amounted to 1,813 tonnes. In June, the capture amounted to 1,605 tonnes. There was a decrease in production volume of 207 tonnes, or about 11%. There are 10 species of fish captured, dominated by tuna